Analisis Pengendalian Kualitas Produk Tahu Goreng dengan Metode Statistical Quality Control (SQC) - Dika Yunita Triamanda; Mega Cattleya PA Islami (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Quality is an important factor for consumers in choosing a product, so maintaining or improving product quality is important for companies to compete and satisfy consumers. Small and Medium Enterprises (SMEs) face challenges in maintaining product quality and therefore require an effective quality control system, one example is Pak Sifa' Fried Tofu UKM in Jombang. By using primary data obtained through interviews and direct observation, Statistical Quality Control (SQC) methods such as check sheets, stratification, scatter diagrams, histograms, control charts, Pareto diagrams, and cause-and-effect diagrams are used for data analysis aimed at identifying types dominant defects in fried tofu products and their causes. The research found that the dominant defect in fried tofu production was split tofu defect with a defect rate of 52.921%. Factors that cause split tofu defects include human factors, methods, measurements, machines, materials and the environment. This research highlights the need for SMEs to prioritize quality improvement strategies, particularly addressing dominant defects and their root causes. Implementing SQC tools can help SMEs improve product quality and reduce defects.